Comparative analysis of financial performance at Bank Syariah Mandiri and Bank BCA Syariah during the covid-19 pandemic - Mila Arumil Jannah; Mahmudah Sa'diyah (NUsantara Islamic Economic Journal, 2022)
This study aims to compare and see the differences in the financial performance of Bank Syariah Mandiri and Bank BCA Syariah on the ratio of Capital Adequacy Ratio (CAR), Return In Assets (ROA), Non Performing Financing (NPF), Operating Costs and Operating Income (BOPO), and Financing to Deposit Ratio (FDR). The method used in this study is a comparative research method with quantitative data analysis using the two-average difference test (Independent Sample T-test). The object of the research is Bank Syariah Mandiri and Bank BCA Syariah, the data used in this study were obtained from published financial reports published by Bank Syariah Mandiri and Bank BCA Syariah in March to December 2020. The results showed that there were significant differences in performance of Bank Syariah Mandiri finance with Bank BCA Syariah for each ratio. In the ratio of Return In Assets (ROA), Non Performing Financing (NPF), Operating Costs and Operating Income (BOPO), and Financing to Deposit Ratio (FDR), Bank Syariah Mandiri's financial performance is better than Bank BCA Syariah. However, the Capital Adequacy Ratio (CAR) of Bank BCA Syariah is better than Bank Syariah Mandiri.